Functional Outcome of Non-operative Method of Treatment in Adult Patients with Proximal Humeral Fracture - Raza Askari, Muhammad Siraj, Kamran Asghar, Waqar Ahmed, Aizaz Ali Shah, Muhammad Ahmed Saleemi, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find the functional-outcomes of non-operative treatment in proximal-humeral fracture of adults. Study Design: Prospective study Place and Duration of Study: Department of Orthopedic, Khyber Teaching Hospital, Peshawar from 1st January 2019 to 31st December 2019. Methodology: One hundred patients age more than 50 years were enrolled. Patients were treated by usage of sling and their clinical as well as radiological imaging was followed until a year. Primary out comes were measured by Oxford-Shoulder Score and EuroQol5 Dimensions3-Levels while secondary through visual-analogue scale and university of California Los Angeles-scoring protocol. Results: There were 73% females and 27% males. OSS and EQ-5D-3L mean score highly reduced as shown by the improved scores of primary outcomes. VAS as secondary outcomes 32.2 at a year time with 59.1 treatment gratification and health score of VAS as 68.1 with 20.5 of UCLA presenting significant improvement and recovery. Conclusion: Non- operative method of treatment is a significant method with efficient recovery outcomes.